Development Of International Bridal Makeup Learning Tools Based On Hybrid Learning - Tobing, Marnala; Nurul Rangkuti, Irmiah; Wahidah, Siti; Vebibina, Almaida; Pujawanti Dhana, Vita (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
This study aims to produce a learning tool for international bridal make-up based on Hybrid Learning by utilizing the SIPDA Unimed Learning Management System. learning tools in the form of Semester Learning Plans, Bridal Make Up E-books with ISBN, International Bridal Make Up Learning Videos. The development model used is the ADDIE development model which consists of 5 (five) steps including: Analysis, Design, Development, and Evaluate. Data collection was carried out through tests of experts (experts) including tests of media experts, design experts and material experts. After evaluation from the experts, it was continued with trials on respondents, namely cosmetology education study program students through individual tests (one to one), small group tests (Small Group) and Field Tests (field tests). The results of the study show that the learning tools developed for international bridal makeup learning are appropriate for use in learning at the Medan State University cosmetology education program. This is shown from the results of data processing (tcount=3.285) at a significance level ɔ = 0.05 with dk 56 obtained (ttable = 1.67), then (tcount > ttable), the effectiveness of using learning tools in an effort to improve learning outcomes is 80 .46%. The results of the study from groups of students who studied using learning tools were 71.72%. From these data it proves that the use of learning tools through the UNIMED SIPDA learning management system is more effective in improving learning outcomes.